The Role of the Family in Forming Children's Religious Identity: A Case Study of Urban Muslim Families in Pamekasan - Mohammad Muchlis Solichin; Nor Hasan; Mohammad Hasan (Pt. Anagata Sembagi Education, 2025)
This study focuses on examining the role of urban Muslim families in shaping adolescents’ religious identity. The research specifically explores: (1) religious parenting patterns, (2) the family atmosphere in fostering religious identity, (3) the religious values taught, (4) the methods of delivering religious teachings, and (5) challenges within the family environment. Employing a qualitative approach, data were collected through direct and participant observation, in-depth interviews, and documentation. Data analysis was conducted in three stages: data reduction, data display, and conclusion drawing and verification. The findings reveal that parents act as primary guides, encouraging and facilitating their children's engagement in religious activities such as attending mosque lectures and participating in religious education. By actively practicing communal worship and leading by example, parents instill a sense of unity and spiritual identity in their children. A nurturing family environment characterized by emotional closeness, open communication, and mutual support significantly contributes to the formation of children's religious identity. In such settings, religion is not merely a ritualistic obligation but serves as a profound source of peace and harmony. Overall, parental involvement through modeling, dialogue, and the integration of Islamic values into daily life plays a crucial role in the spiritual development of children.